Generalized pustular psoriasis: overview of the status quo and results of a panel discussion. (8th June 2022) - Reich, Kristian; Augustin, Matthias; Gerdes, Sascha; Ghoreschi, Kamran; Kokolakis, Georgios; Mößner, Rotraut; Mrowietz, Ulrich; Navarini, Alexander A.; Pinter, Andreas; Schäkel, Knut; Staubach, Petra; Sticherling, Michael; et al.
Summary: Generalized pustular psoriasis (GPP) is a rare, severe, potentially life‐threatening, autoinflammatory, neutrophilic skin disease that may be accompanied by fever and leukocytosis. This paper describes the current state of knowledge on GPP in terms of classification, (differential) diagnosis and prevalence. We present a comparison of the genetics and pathoimmunology of GPP and psoriasis vulgaris with the central mechanisms of autoimmunology and autoinflammation. The currently available therapeutic options, expert recommendations for therapy, and data from early clinical trials investigating targeted therapies will be summarized. We present the results of our discussion with 13 experts for psoriasis vulgaris and GPP and give an integrated overview of indication and therapy based on our personal experience and present an outlook on further research questions. Collectively, this article highlights the high unmet need in GPP, as there exists no satisfactory method of diagnosis or treatment to date and new treatment options will be of great therapeutic benefit to those affected.